Pratiques d’ergonomes et dynamiques de transformation dans le cadre de l’expertise SSCT pour les CSE - Claire Violleau; Bernard Dugué (Activités)
HSWC expertise- now CSE expertise (social and economic committees in French companies) in Health, Safety and Working Conditions- is a form of ergonomics practice. Ergonomics is not the only discipline to intervene in this context but we assume that it responds with specificities contributing to the implementation of transformations. Our analyses, based on the study of several cases of intervention in the context of “important project” expertise, demonstrate that transformations are possible and varied with regard to : social relations, the representations of actors, their modes of interaction and the ergonomists themselves. The latter’s position is also a key element in the success of an expertise. So if this mode of intervention is often a source of criticism in ergonomics, it is undoubtedly due to the nature of its less visible transformations, which are not necessarily technical, material or organizational but above all deeply social.